Opt-out provider-initiated HIV testing and counselling in primary care outpatient clinics in Zambia - Stephanie M Topp; Julien M Chipukuma; Matimba M Chiko; Chibesa S Wamulume; Carolyn Bolton-Moore; Stewart E Reid (The World Health Organization, 2011)
OBJECTIVE: To increase case-finding of infection with human immunodeficiency virus (HIV) in Zambia and their referral to HIV care and treatment by supplementing existing client-initiated voluntary counselling and testing (VCT), the dominant mode of HIV testing in the country. METHODS: Lay counsellors offered provider-initiated HIV testing and counselling (PITC) to all outpatients who attended primary clinics and did not know their HIV serostatus. Data on counselling and testing were collected in registers. Outcomes of interest included HIV testing coverage, the acceptability of testing, the proportion testing HIV-positive (HIV+), the proportion enrolling in HIV care and treatment and the time between testing and enrolment. FINDINGS: After the addition of PITC to VCT, the number tested for HIV infection in the nine clinics was twice the number undergoing VCT alone. Over 30 months, 44 420 patients were counselled under PITC and 31 197 patients, 44% of them men, accepted testing. Of those tested, 21% (6572) were HIV+; 38% of these HIV+ patients (2515) enrolled in HIV care and treatment. The median time between testing and enrolment was 6 days. The acceptability of testing rose over time. CONCLUSION: The introduction of routine PITC using lay counsellors into health-care clinics in Lusaka, Zambia, dramatically increased the uptake and acceptability of HIV testing. Moreover, PITC was incorporated rapidly into primary care outpatient departments. Maximizing the number of patients who proceed to HIV care and treatment remains a challenge and warrants further research.